SOCIAL EMPOWERMENT THROUGH TECHNOLOGICAL INNOVATION FOR SUSTAINABLE AGRICULTURE - Revita, Natasya; Haiah, Fithri (LPPM Universitas Bina Bangsa, 2025)
This is to describe social empowerment through technological innovation in achieving sustainable agriculture. Method used is a descriptive method with a literature approach, analyzing 50 international and national journals that have been published online. Before publication, this paper was discussed with peers and colleagues to obtain constructive input. After making revisions based on these suggestions, this paper was published to contribute to the development of knowledge in the fields of agriculture and technology. Based on the results of the literature analysis, it can be concluded that social empowerment through technological innovation in sustainable agriculture includes: first, increasing farmers' access to information and communication technology; second, development of agricultural applications that support data-based decision making; third, training farmers in the use of modern technology; and fourth, collaboration between farmers, educational institutions and the private sector to create a sustainable agricultural ecosystem. The recommendation of this research is that all relevant parties, including the government and the private sector, invest in the education and training of farmers, so that they can take advantage of technological innovation to increase agricultural sustainability and productivity.